En Masse Resection of Pancreas, Spleen, Celiac Axis, Stomach, Kidney, Adrenal, and Colon for Invasive Pancreatic Corpus and Tail Tumor. (15th September 2013) - Kutluturk, Koray; Alam, Abdul Hamid; Kayaalp, Cuneyt; Otan, Emrah; Aydin, Cemalettin
Abstract : Providing a more comfortable life and a longer survival for pancreatic corpus/tail tumors without metastasis depends on the complete resection. Recently, distal pancreatectomy with celiac axis resection was reported as a feasible and favorable method in selected pancreatic corpus/tail tumors which had invaded the celiac axis. Additional organ resections to the celiac axis were rarely required, and when necessary it was included only a single extra organ resection such as adrenal or intestine. Here, we described a distal pancreatic tumor invading most of the neighboring organs—stomach, celiac axis, left renal vein, left adrenal gland, and splenic flexure were treated by en bloc resection of all these organs. The patient was a 60-year-old man without any severe medical comorbidities. Postoperative course of the patient was uneventful, and he was discharged on postoperative day eight without any complication. Histopathology and stage of the tumor were adenocarcinoma and T4 N1 M0, respectively. Preoperative back pain of the patient was completely relieved in the postoperative period. As a result, celiac axis resection for pancreatic cancer is an extensive surgery, and a combined en masse resection of the invaded neighboring organs is a more extensive surgery than the celiac axis resection alone. This more extensive surgery is safe and feasible for selected patients with pancreatic cancer.